2002
DOI: 10.1248/bpb.25.68
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Kalopanaxsaponin K by Human Intestinal Bacteria and Antirheumatoid Arthritis Activity of Their Metabolites.

Abstract: The stem bark of Kalopanax pictus belonging to the family Araliaceae has been used in Korea as a tonic, analgesic, antiinflammatory and antidiabetic medicine. From this plant, hederagenin glycosides, syringin, liriodendrin, and coniferylaldehyde glucosides have been isolated. [1][2][3] Related to biological activities of K. pictus, it was reported that the active components on antidiabetic, 4) cytotoxic, 5) and antifungal assays 6) may be hederagenin monodesmosides. We also reported that kalopanaxsaponin B (KP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Furthermore, as we previously reported, triterpenoid glycosides exhibit bioactivity via the enzymatic hydrolysis of glycosidic sugar chains by human intestinal bacteria. 16) In conclusion, the present results suggest that the four triterpenoids of the root of R. rugosa are responsible for the antiinflammatory activity. In particular, euscaphic acid and tormentic acid had more potent antinociceptive/antiinflammatory effects than the corresponding 28-O-glycosides, kaji-ichigoside F 1 and rosamultin.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, as we previously reported, triterpenoid glycosides exhibit bioactivity via the enzymatic hydrolysis of glycosidic sugar chains by human intestinal bacteria. 16) In conclusion, the present results suggest that the four triterpenoids of the root of R. rugosa are responsible for the antiinflammatory activity. In particular, euscaphic acid and tormentic acid had more potent antinociceptive/antiinflammatory effects than the corresponding 28-O-glycosides, kaji-ichigoside F 1 and rosamultin.…”
Section: Resultssupporting
confidence: 54%
“…We previously reported that the compounds obtained from the hydrolysis of the triterpenoid glycosides (kalopanaxsaponins B and K) exert significant bioactivities. 15,16) Four compounds were tested for antiinflammatory and antinociceptive activity in rats and mice. As shown in Table 3, the antinociceptive effects of the triterpene glycosides (1, 2) was mild to significant at oral dosages of 20 and 30 mg/kg, whereas euscaphic acid (3) and tormentic acid (4) had a pronounced effect.…”
Section: Resultsmentioning
confidence: 99%
“…The other constituent of KP, α-hederin methyl ester, showed anticarrageenan activity in rats and anti-arthritic activity in rats and mice (15). Kalopanaxsaponin A was reported to have anti-rheumatoidal (16-19), anti-tumor (20), anti-diabetic (21), antifungal (22) activities. Kalopanaxsaponins A inhibits the production of NO, prostaglandin E2 (PGE2) and TNF-α in macrophage cell line RAW 264.7 (1).…”
Section: Discussionmentioning
confidence: 99%
“…administration. 7) Since the triterpenoids are usually more active than the corresponding glycosides, 8,9) we hydrolyzed the active niga-ichigoside F 1 (1) to produce a 23-hydroxytormentic acid (1a). Unlike the experimental design undertaken by Niero et al, 7) we orally administered niga-ichigoside F 1 obtained from R. coreanus and the aglycone 23-hydroxytormentic acid in the present study and compared their antinociceptive and antiinflammatory activities.…”
mentioning
confidence: 99%